Rearmament with a purpose - Mikkel Vedby Rasmussen (EconPol Forum, 2024)
European countries are investing in heavier, platform-centric forces that rely on technology rather than personnel. Europe must develop military R&D to avoid investing in existing technologies at the expense of future capabilities. European governments should focus on acquiring the necessary capabilities to realize strategic objectives rather than focusing solely on the percentage of GDP spent on defense. European governments must invest in armed forces that can be sustained after future funds for rearmament are redistributed. European governments must develop strategic thinking, individually and collectively, to prioritize the development and sustainment of future military capabilities.
Keywords: 330